Antiepileptic effect of acylpolyaminetoxin JSTX-3 on rat hippocampal CA1 neurons in vitro - Salamoni, S. D.; da Costa, J. C.; Palma, Mario Sergio [UNESP]; Konno, K.; Nihei, K.; Tavares, A. A.; de Abreu, D. S.; Venturin, G. T.; Cunha, F. D.; de Oliveira, R. M.; Breda, R. V. (Elsevier B.V., 2005)
The Joro spider toxin (JSTX-3), derived from Nephila clavata, has been found to block glutamate excitatory activity. Epilepsy has been studied in vitro, mostly on rat hippocampus, through brain slices techniques. The aim of this study is to verify the effect of the JSTX-3 on the epileptiform activity induced by magnesium-free medium in rat CA1 hippocampal neurons. Experiments were performed on hippocampus slices of control and pilocarpine-treated Wistar rats, prepared and maintained in vitro. Epileptiform activity was induced through omission of magnesium from the artificial cerebrospinal fluid (0-Mg2+ ACSF) superfusate and iontophoretic application of N-methyl-D-aspartate (NMDA). Intracellular recordings were obtained from CA] pyramidal neurons both of control and epileptic rats. Passive membrane properties were analyzed before and after perfusion with the 0-Mg2+ ACSF and the application of toxin JSTX-3. During the ictal-like activity, the toxin JSTX-3 was applied by pressure ejection, abolishing this activity. This effect was completely reversed during the washout period 2. when the slices were formerly perfused with artificial cerebrospinal fluid (ACSF) and again with 0-Mg2+ ACSF. Our results suggest that the toxin JSTX-3 is a potent blocker of induced epileptiform activity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: JSTX-3; pilocarpine; epilepsy; NMDA; hippocampus